Spatial analysis of coastal environments - Hamylton, Sarah M. (UK: CUP, 2017)
This book explains how the many varied forms of spatial analysis, including mapping, monitoring and modelling, can be applied to a range of coastal environments such as estuaries, mangroves, seagrass beds and coral reefs. Presenting empirical geographical approaches to modelling, which draw on recent developments in remote sensing technology, geographical information science and spatial statistics, it provides the analytical tools to map, monitor and explain or predict coastal features. With detailed case studies and accompanying online practical exercises, it is an ideal resource for undergraduate courses in spatial science. Taking a broad view of spatial analysis and covering basic and advanced analytical areas such as spatial data and geostatistics, it is also a useful reference for ecologists, geomorphologists, geographers and modellers interested in understanding coastal environments.
1 - The Application of Spatial Analysis to Coastal Environments -- 2 - The Nature of Spatial Data -- 3 - Basic Geographical Analysis With Spatial Information in Coastal Environments -- 4 - Mapping Coastal Environments -- 5 - Monitoring Coastal Environments -- 6 - Geostatistical Analysis of Coastal Environments -- 7 - Modelling Coastal Environments -- 8 - Addressing Uncertainty in the Spatial Analysis of Coastal Environments -- 9 - Communicating and Incorporating the Results of Spatial Analysis Successfully
Includes bibliographical references, glossary and index
Keywords: Environmental Sciences -- Earth; Environmental Sciences -- Coastal; Remote Sensing; GIS; Oceanography; Marine Science